Parasite clearance, cure rate, post-treatment prophylaxis and safety of standard 3-day versus an extended 6-day treatment of artemether–lumefantrine and a single low-dose primaquine for uncomplicated Plasmodium falciparum malaria in Bagamoyo district, Tanzania: a randomized controlled trial - Lwidiko E. Mhamilawa (Malaria Journal, 2020)
Abstract Background Artemisinin-based combination therapy (ACT) resistant Plasmodium falciparum represents an increasing threat to Africa. Extended ACT regimens from standard 3 to 6 days may represent a means to prevent its development and potential spread in Africa. Methods Standard 3-day treatment with artemether–lumefantrine (control) was compared to extended 6-day treatment and single low-dose primaquine (intervention); in a randomized controlled, parallel group, superiority clinical trial of patients aged 1–65 years with microscopy confirmed uncomplicated P. falciparum malaria, enrolled in Bagamoyo district, Tanzania. The study evaluated parasite clearance, including proportion of PCR detectable P. falciparum on days 5 and 7 (primary endpoint), cure rate, post-treatment prophylaxis, safety and tolerability. Clinical, and laboratory assessments, including ECG were conducted during 42 days of follow-up. Blood samples were collected for parasite detection (by microscopy and PCR), molecular genotyping and pharmacokinetic analyses. Kaplan–Meier survival analyses were done for both parasite clearance and recurrence. Results A total of 280 patients were enrolled, 141 and 139 in the control and intervention arm, respectively, of whom 121 completed 42 days follow-up in each arm. There was no difference in proportion of PCR positivity across the arms at day 5 (80/130 (61.5%) vs 89/134 (66.4%), p = 0.44), or day 7 (71/129 (55.0%) vs 70/134 (52.2%), p = 0.71). Day 42 microscopy determined cure rates (PCR adjusted) were 97.4% (100/103) and 98.3% (110/112), p = 0.65, in the control and intervention arm, respectively. Microscopy determined crude recurrent parasitaemia during follow-up was 21/121 (17.4%) in the control and 14/121 (11.6%) in the intervention arm, p = 0.20, and it took 34 days and 42 days in the respective arms for 90% of the patients to remain without recurrent parasitaemia. Lumefantrine exposure was significantly higher in intervention arm from D3 to D42, but cardiac, biochemical and haematological safety was high and similar in both arms. Conclusion Extended 6-day artemether–lumefantrine treatment and a single low-dose of primaquine was not superior to standard 3-day treatment for ACT sensitive P. falciparum infections but, importantly, equally efficacious and safe. Thus, extended artemether–lumefantrine treatment may be considered as a future treatment regimen for ACT resistant P. falciparum, to prolong the therapeutic lifespan of ACT in Africa. Trial registration ClinicalTrials.gov, NCT03241901. Registered July 27, 2017 https://clinicaltrials.gov/show/NCT03241901